2014
DOI: 10.1111/jac.12082
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Cold Resistance in Plants

Abstract: Cold is a typical environmental stress factor that limits the geographical distribution and growth of various plants. It affects crop quality and productivity. In the contemporary years, with the plant cold‐resistant genetic engineering development, great progress was obtained in this field. This paper gave a general statement about the development of plant cold resistantance on the level of unsaturated fatty acids, protective enzymes, functional genes and regulation genes, aiming to provide some useful inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 89 publications
0
43
0
1
Order By: Relevance
“…Sugar accumulation enhances cold tolerance in Miscanthus ( Purdy et al , 2013 ) as well as in other species including Arabidopsis ( Kaplan and Guy, 2004 , 2005 ; Yano et al , 2005 ), maize ( Hodges et al , 1997 ), sunflower ( Paul et al , 1991 ), and sugarcane ( Du and Nose, 2002 ). At subzero temperatures, sugars will modulate tissue osmolarity, thus helping to maintain the membrane stability ( Jonak et al , 1996 ; Chen et al , 2014 ). In the continuous-cooling rate study of August 2010, the diploids had similar LT 50 values to those measured in winter, while the rhizomes from triploid and tetraploid lines exhibited LT 50 values that were significantly warmer than their corresponding winter values.…”
Section: Discussionmentioning
confidence: 99%
“…Sugar accumulation enhances cold tolerance in Miscanthus ( Purdy et al , 2013 ) as well as in other species including Arabidopsis ( Kaplan and Guy, 2004 , 2005 ; Yano et al , 2005 ), maize ( Hodges et al , 1997 ), sunflower ( Paul et al , 1991 ), and sugarcane ( Du and Nose, 2002 ). At subzero temperatures, sugars will modulate tissue osmolarity, thus helping to maintain the membrane stability ( Jonak et al , 1996 ; Chen et al , 2014 ). In the continuous-cooling rate study of August 2010, the diploids had similar LT 50 values to those measured in winter, while the rhizomes from triploid and tetraploid lines exhibited LT 50 values that were significantly warmer than their corresponding winter values.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the southern seeds had higher percentages of UFAs (88.44±0.19 %) and PUFAs (79.69±0.34 %). Many studies have demonstrated that FA contents, especially contents of UFAs in the lipids of cytomembranes, are the results of adaptive evolution of plants in response to environmental changes of their habitats, and are evidenced to be positively correlated to the fluidity of cytomembranes and the cold tolerance of plants [36] . The differences of FA profiles between T. sinensis seeds may be related to their geographical distributions, for the northern sites are much colder than the southern sites, and the northern seeds contain much higher contents (but lower percentages) of UFAs than the southern seeds.…”
Section: Resultsmentioning
confidence: 99%
“…especially contents of UFAs in the lipids of cytomembranes, are the results of adaptive evolution of plants in response to environmental changes of their habitats, and are evidenced to be positively correlated to the fluidity of cytomembranes and the cold tolerance of plants. [36] The differences of FA profiles between T. sinensis seeds may be related to their geographical distributions, for the northern sites are much colder than the southern sites, and the northern seeds contain much higher contents (but lower percentages) of UFAs than the southern seeds. Thus, the FA profiles of T. sinensis seeds can potentially be used to distinguish seed provenance between northern or southern production areas and help farmers avoid purchasing inappropriate seeds for local cultivations.…”
Section: Composition and Content Of Fas In T Sinensis Seedsmentioning
confidence: 99%
“…ROS causes membrane lipid peroxidation and results in accumulation of MDA (Chen & Zhang, 2016). Higher plants possess active oxygen scavenging systems, including several antioxidant enzymes, such as SOD, CAT and POD to counterbalance the ROS formation (Chen et al, 2014;. SOD is responsible for catalysing the disproportionation of singlet oxygen to H 2 O 2 , then POD and CAT decompose H 2 O 2 to H 2 O and O 2 (Keunen et al, 2013;Li et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%